478OPhase II study of fruquintinib plus gefitinib in stage IIIb/IV NSCLC patients harboring EGFR activating mutations. (24th November 2019) - Lu, S; Zhou, J; Niu, X; Chen, Y; Su, W
Abstract: Background: Fruquintinib is a potent and highly selective oral small molecule tyrosine kinase inhibitor of VEGFR. Preclinical data showed that a combined blockade of VEGFR and EGFR had synergistic antitumor effects. In the JO25567 trial, bevacizumab plus erlotinib had significantly prolonged median progression-free survival (PFS) in EGFR mutant NSCLC patients. Approaching this combined blockade with two oral drugs may improve ease of use for patients and greater therapeutic flexibility for physicians, while the high selectivity and shorter half-life of fruquintinib vs. a VEGF antibody may provide a better safety profile. Methods: This is a single arm, open-label, multi-center, 2-cohort study in first line EGFR mutant NSCLC patients (NCT02976116). All patients receive 250 mg QD gefitinib (Gefi) continuously. Fruquintinib (Fruq) is given at 4 mg QD for 3 weeks followed by 1 week off in the first 4-week cycle. In cohort 1 the fruquintinib dose is escalated to 5 mg under the same 4-week cycle if no ≥grade 3 adverse event (AE) or ≥grades 2 liver dysfunction occurs in the first cycle. In cohort 2 fruquintinib remains at 4 mg. The primary objective is to assess the efficacy (objective response rate, ORR) and tolerability of this combination. The secondary objective is to assess PFS. Results: As of July 5, 2019, 26 and 24 patients have been enrolled in cohort 1 and cohort 2, respectively, and received at least one dose of each drug. Among them 26 had L858R mutation, and 24 had exon 19 deletions. The efficacy and safety data are summarized in the table below. Conclusions: Fruquintinib plus gefitinib showed an overall acceptable safety profile and promising efficacy. 4 mg of fruquintinib (in combination with 250 mg of gefitinib) was better tolerated than 5 mg, without compromising efficacy. Confirmatory studies at this recommended dose are required to further verify the full potential of this treatment. Clinical trial identification: NCT02976116. Legal entity responsible for the study: Hutchison MediPharma. Funding: Hutchison MediPharma. Disclosure: S. Lu: Advisory / Consultancy: Hutchison MediPharma. Y. Chen: Full / Part-time employment: Hutchison MediPharma. W. Su: Full / Part-time employment: Hutchison MediPharma. All other authors have declared no conflicts of interest.